Akibat Hukum Yang Timbul Dari Perceraian Beda Kewarganegaraan Perspektif Hukum Perdata Internasional - Azizah Rima Gitacahyani; Bilqis Dewi P; Cherisanda Nesya; Regita Kisnanda Putri; Yasmine Erlisa (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Divorce between spouses of different nationalities has become an increasingly common phenomenon in the context of globalization. International civil law plays a key role in addressing the legal issues arising from divorce between different nationalities. This article discusses the legal repercussions arising from such divorces, focusing on several important aspects. Determination of the applicable law is a major concern in cases of non-citizenship divorce. The Lex Loci principle is the rule used to determine the law governing divorce, with special considerations regarding both spouses being from different countries. The recognition of divorce in different jurisdictions is an important concern. The process of official recognition of divorce in different countries often requires special procedures and certain requirements. Issues related to child custody become particularly significant if the couple has children together. International civil law considers aspects such as child residence, custody, and child-related decision-making. A valid divorce certificate may be required for various purposes, including a change in marital status in each spouse's country. The process of obtaining a divorce certificate may vary in each spouse's home country. Pensions and inheritance may also be affected by divorce, and the application of international civil law principles is necessary to determine the associated rights.